Development of biodegradable polymer composites - Ruan, Wei. (2013)
Poly (lactic acid) (PLA) is a well-known biodegradable polymer. It can be obtained from the renewable agricultural crop such as corn, potatoes and waste produce. Recently, PLA has garnered a lot of attention as a result of growing environmental awareness.